Acantholytic dyskeratotic acanthoma: case report and review of the literature - Alina Goldenberg; Robert A. Lee; Philip R. Cohen (Mattioli1885, 2014)
Background: Focal acantholytic dyskeratosis has been described as an incidental finding and as a clinically distinct lesion. In both situations, a dimorphic histologic pattern is observed: acantholysis and dyskeratosis. Solitary, non-genital lesions displaying such pathology have been difficult to classify. Clinical and pathological characteristics of acantholytic dyskeratotic acanthomas are described. Methods: The features of a patient with solitary, non-genital, acantholytic dyskeratotic acanthoma are presented and the literature on acantholytic dyskeratotic acanthomas is reviewed. Using PubMed the following terms were searched and relevant citations assessed: acantholysis, acanthoma, cutaneous, dyskeratosis, nail, warty. Results: We identified 30 cutaneous acantholytic dyskeratotic acanthomas, including our patient, most often found on the trunk and mimicking basal cell carcinoma, and three subungual acantholytic dyskeratotic acanthomas of the thumb, which mimicked onychopapilloma. Conclusion: Acantholytic dyskeratotic acanthomas are clinically and pathologically distinct lesions, which may morphologically present as either truncal plaques or subungual longitudinal erythronychia.